2013
DOI: 10.1523/jneurosci.5563-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric G Protein Subunit Gγ13 Is Critical to Olfaction

Abstract: The activation of G-protein-coupled olfactory receptors on the olfactory sensory neurons (OSNs) triggers a signaling cascade, which is mediated by a heterotrimeric G protein consisting of α, β and γ subunits. Although its α subunit, Gαolf, has been identified and well characterized, the identities of its β and γ subunits and their function in olfactory signal transduction, however, have not been well established yet. We and others have found the expression of Gγ13 in the olfactory epithelium, particularly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 57 publications
9
55
0
2
Order By: Relevance
“…We therefore asked whether odor-induced cAMP signaling is required for establishing the cilia pattern. We first examined olfactory epithelia from Gγ13 −/− mice, in which Cre-mediated ablation of Gγ13 prevents proper formation and ciliary targeting of G olf in OSNs and eliminates odor-induced electroolfactogram (EOG) signals [32]. Surprisingly, the cilia pattern remains completely intact in these animals (Figure 4A–C and Table S2), suggesting that G olf -mediated activity is not required for the formation and maintenance of the cilia pattern.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore asked whether odor-induced cAMP signaling is required for establishing the cilia pattern. We first examined olfactory epithelia from Gγ13 −/− mice, in which Cre-mediated ablation of Gγ13 prevents proper formation and ciliary targeting of G olf in OSNs and eliminates odor-induced electroolfactogram (EOG) signals [32]. Surprisingly, the cilia pattern remains completely intact in these animals (Figure 4A–C and Table S2), suggesting that G olf -mediated activity is not required for the formation and maintenance of the cilia pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, conditional knockout of Gγ 13 in mouse olfactory sensory neurons results in dramatic down-regulation of Gα olf , Gβ 1 and the guanine nucleotide exchange factor RIC8B, as well as mislocalization of type III adenylyl cyclase to the sensory neuron soma (Li et al, 2013). In contrast, Gα olf and Gβ 1 expression is unaffected by inhibition of Gβγ signaling in zebrafish olfactory sensory neurons (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Ryba and Tirindelli (1995) reported the expression of Gγ 8 gene transcript in cell bodies of immature OSNs (iOSNs) using RNA in situ hybridization (RISH). In addition, Gγ 13 protein is known to express strongly in cilia and cell bodies of mOSNs in the MOE, including a subset of OSNs that express TRPM5, and plays an important role in olfaction (Kulaga et al, 2004; Lin et al, 2007; Li et al, 2013). More recently, Kerr et al (2008) reported that Gβ 1 was the dominant Gβ subunit in the MOE.…”
Section: Introductionmentioning
confidence: 99%